Effects of cyclic adenosine monophosphate modulators on maturation and quality of vitrified-warmed germinal vesicle stage mouse oocytes - Dayong Lee; Hyang Heun Lee; Jung Ryeol Lee; Chang Suk Suh; Seok Hyun Kim; S. Samuel Kim (BMC, 2020)
Abstract Background It is still one of the unresolved issues if germinal vesicle stage (GV) oocytes can be successfully cryopreserved for fertility preservation and matured in vitro without damage after warming. Several studies have reported that the addition of cyclic adenosine monophosphate (cAMP) modulators to in vitro maturation (IVM) media improved the developmental potency of mature oocytes though vitrification itself provokes cAMP depletion. We evaluated whether the addition of cAMP modulators after GV oocytes retrieval before vitrification enhances maturation and developmental capability after warming of GV oocytes. Methods Retrieved GV oocytes of mice were divided into cumulus-oocyte complexes (COCs) and denuded oocytes (DOs). Then, GV oocytes were cultured with or without dibutyryl-cAMP (dbcAMP, cAMP analog) and 3-isobutyl-l-methylxanthine (phosphodiesterase inhibitor) during the pre-vitrification period for 30 min. Results One hour after warming, the ratio of oocytes that stayed in the intact GV stage was significantly higher in groups treated with cAMP modulators. After 18 h of IVM, the percentage of maturation was significantly higher in the COC group treated with dbcAMP. The expression of F-actin, which is involved in meiotic spindle migration and chromosomal translocation, is likewise increased in this group. However, there was no difference in chromosome and spindle organization integrity or developmental competence between the MII oocytes of all groups. Conclusions Increasing the intracellular cAMP level before vitrification of the GV oocytes maintained the cell cycle arrest, and this process may facilitate oocyte maturation after IVM by preventing cryodamage and synchronizing maturation between nuclear and cytoplasmic components. The role of cumulus cells seems to be essential for this mechanism.